Forcing of bulbs of selected species of geophytes for earlier sale - Mihael Kušen; Tatjana Prebeg; Vesna Židovec (Glasnik Zaštite Bilja, 2023)
The ornamental plant market is short on supply of flowering species during the late autumn and winter period, and demand increases during the Christmas holidays. Cultivation of cold-resistant geophytes that spent the summer dormant and formed flower buds for the next season is relatively simple and falls at a time when protected areas for seasonal production are not used to their maximum capacity. The aim of this paper is to explain the life cycle of geophytes that form flowers during the summer, and the procedures for obtaining flowering potted plants for the late autumn and winter period when there is a lack of such species on the market. Using the example of hyacinths and daffodils, as species that are represented in greater numbers on the European market, and which spend an apparent rest during the summer, the procedure of pre-treatment with cold and cultivation in a protected area for the production of flowering potted plants as well as plants for cutting is explained